Urban vulnerability and adaptation strategies in secondary cities in Chad: Analysis of the case of the city of Pala - Patouki, Sing-non Bourdannet; Ndonaye, Allarané; Kinyui, Nyiniwou Ismaila; Romaric, Djedanoum; Follygan, Hetcheli (Edelweiss Applied Science and Technology, 2025)
This study assesses urban vulnerability from various angles in the city of Pala, Chad. To this end, we conducted a household survey of 340 residents in the city’s 27 neighborhoods. The methodology used is based on a mixed approach that treats both qualitative and quantitative data. Thus, we targeted a number of indicators in the socio-economic field, exposure to risk and natural disasters, architecture, equipment provision, and finally, local adaptation capacities. The analyses showed that, in the absence of a drainage system in the city of Pala, 60% of respondents are vulnerable during the rainy season, compared to 40% who benefit from natural water runoff slopes. Simplistic analyses of satellite images of the waterways crossing the city show that any household located within a 60-meter radius of a waterway is vulnerable, given the city’s high rainfall (where annual rainfall can reach 700 mm or more). Pearson’s test (r=0.55) shows that climatic and environmental factors are also decisive. Economic vulnerability is characterized by the fact that more than 50% of this population lives on less than 1 per day. Architectural vulnerability is reflected in the precariousness of traditional building materials, which are exposed to various risks. The value of this research is not limited to understanding urban vulnerability in general, as it also sheds light on issues of resilience through local practices.